KECERDASAN INTERPERSONAL TOKOH DALAM NOVEL ANAK DUNIA KECIL MIMPI HIDUP DI MATA SI KECIL KARYA YOYON INDRA JONI - Herma, .; Priyadi, A. Totok; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstrak:Research in the novel "Interpersonal intelligence figures in the novel Dunia Kecil Mimpi Hidup di Mata Si Kecilby Yoyon Indra Joni" background for introducing children's literature both orally and in writing. The problem in this research is how interpersonal main character and supporting cast as well as the implementation of the plan of learning in children's novel Dunia Kecil Mimpi Hidup di Mata Si Kecilby Yoyon Indra Joni? Of these problems, this study aims to describe the main character and interpersonal intelligence supporting cast as well as its implementation into lesson plans. The benefits of this theoretical study is to increase the amount of research related to psychology and can support the psychological theory of literature. While practically this research can be input for further research and provide knowledge to all people. This study uses the theory of Garner, Binet, Buzan, Ormrod and Sarwono. The all process of data collection in this research use descriptive method with qualitative terms. The approach used is psikolanalitik approach. While the data source is novel Dunia Kecil Mimpi Hidup di Mata Si Kecil by Yoyon Indra Joni. The data taken is in the form of words, phrases or sentences contained in the novel. Techniques used in data collection is a study technique documentary by the author as a key or a main instrument. Test the validity of the author's data required for thorough and diligent in analyzing the data so that the necessary triangulation and adequacy of reference. Data analysis technique is done in a way describe, analyze, interpret and make verification / conclusions. Based on research by the author, there are some conclusions of this study, ie. 1) The existence of interpersonal intelligence that experienced by the main character in the interaction that occurs in the novel Dunia Kecil Mimpi Hidup di Mata Si Kecilby YoyonIndra Joni. 2) The existence of interpersonal intelligence experienced supporting cast in the interaction that occurs in the novel Dunia Kecil Mimpi Hidup di Mata Si Kecilby YoyonIndra Joni. 3) This researchcan be implemented in a high school class XII learning in the second half. Keywords: intelligenc,interpersonal, figuresand, novel.